A Newborn with Right Eye Proptosis Secondary to Lymphangioma: A Case Report - Reza Sharafi; Afagh Hassanzadeh Rad (Mashhad University of Medical Sciences, 2016)
Background: Lymphangiomas are relatively rare, benign, congenital malformations, which may affect the conjunctiva, lids and orbit of the eyes. Lymphangiomas are commonly located behind the orbital septum and usually manifest with proptosis, as well as the pain caused by spontaneous intralesional hemorrhage or upper respiratory infection. Previous studies have proposed the major causes of neonatal proptosis. In this article, we present the case of a female neonate born to a mother with triplet pregnancy. On day 28 of birth, clinicians were concerned about the proptosis in the right eye of the second sibling, and the neonate was evaluated via repeated ultrasound. The infant had good general appearance, and after ophthalmological consultation, both neonates were discharged on day 30 of birth. According to clinicians, the right eye proptosis was possibly caused by a benign lesion, such as lymphangioma. Moreover, it was noted that the proptosis would be absorbed gradually, and no interventions were required for the neonate. As predicted, the proptosis was completely absorbed at two months of age. Therefore, it is recommended that clinicians consider benign causes for neonatal proptosis, such as lymphangioma originating from neonatal sepsis.